PEMODELAN 2D DATA GROUND PENETRATING RADAR (GPR) PADA LAHAN GAMBUT DI DESA JATI MULYO - Dewi, Ira Kusuma; Adriansyah, Riadi (JOURNAL ONLINE OF PHYSICS, 2023)
Research has been conducted using the ground penetrating radar (GPR) method which aims to determine subsurface lithology on peatlands in Jati Mulyo Village based on 2D modeling. The GPR method is one of the geophysical methods that applies electromagnetic wave propagation. GPR data measurements were carried out as many as 3 passes with each length of 200 meters. The result of the GPR measurement is a 2D model that describes subsurface lithology. The response of this 2D model is in the form of a distribution of color variations starting from yellow-red, green, light blue -dark blue. The yellow-orange color response indicates the presence of minerals found on peatlands. The green response describes the soil below the surface. While the blue response indicates a cavity filled with water. This is appropriate based on the geology of this peatland is a sedimentary deposit that has pores filled with water and the presence of mineral content contained in the peat soil. Â Â 